Design, finite element analysis, fabrication and electroacoustic characterization of transducer arrays from piezoceramics with hollow cylindrical shell form - Boz, Muhammet; Kaya, Mustafa Yunus; Ozdemir, Omer; Alkoy, Sedat (Taylor & Francis Ltd, 2022)
Electroacoustic transducers arrays operating in the 50-100 kHz frequency range are currently being investigated for underwater applications such as target detection transducers installed on underwater autonomous vehicles (UAV) and detection of underwater intruders to protect and secure economically and strategically critical coastal areas and facilities. However, the frequency range is such that it prevents the use of monolithic piezoceramics operating in the thickness mode due to the unacceptably high voltages that are required to drive them. Whereas the alternative such as Langevin-type transducer solutions have certain other assembly difficulties that arise due to the size limitations imposed on the transducer from the half-wavelength (lambda/2) arrangement requirement of the units. In our study, an entirely new alternative was proposed to overcome these difficulties. A piezoceramic transducer constructed from a hollow cylindrical shell form poled in the radial direction was designed and developed to operate at the longitudinal length extension mode. Since the hollow cylindrical piezoceramics were designed and produced with one end closed, this closed end was used as a passive cap with the transducer operating in a piston mode. ATILA finite element analysis code was used to design, analyze and fine-tune the dimensional requirements of the transducer. The center frequency of the transducer was fixed to 70 kHz. Commercial lead zirconate titanate (PZT) composition with hard piezoelectric character (PZT-4) was used as the starting powder. The slip casting method was used to obtain the cylindrical shell form. Single element transducers, as well as a hexagonal close-packed array consisting of seven units and arranged with a distance of half-wavelength (lambda/2) to obtain constructive interference at 70 kHz were constructed and tested for underwater electroacoustic performance.
Keywords: Piezoelectric; cylindrical; transducer; PZT; FEA